Designing small-sided games for training tactical aspects in soccer: Extrapolating pitch sizes from full-size professional matches - Fradua, L.; Zubillaga, A.; Caro, O.; Fernández-Garcia, A. I.; Ruiz-Ruiz, C.; Tenga, A. (Journal of Sports Sciences, 2013)
The aims of this study were to examine the 1) individual playing area, 2) length and width of the rectangle encompassing the individual playing area and 3) distance between the goalkeepers and their nearest team-mates during professional soccer matches and compare these to previously reported pitch sizes for small-sided games (SSGs). Data were collected from four Spanish La Liga matches of the 2002-03 season, and notated post-event using the Amisco® system. The pitch sizes obtained from real matches were smaller and different from those used previously for SSGs. In addition, the current pitch sizes show significant (P < 0.001) effect of ball location in all variables examined. For example, overall individual playing area (F [5, 2562] = 19.99, P < 0.001, ?2 = 0.04) varied significantly across six different zones of the pitch. Based on these empirical results, pitch sizes with individual playing areas ranging from 65 m2 to 110 m2 and length to width ratio of 1:1 and 1:1.3 are generally recommended for training tactical aspects according to different phases of play. It is possible to design SSGs with a more valid representation of the tactical conditions experienced in full-size matches and their use may improve the training effect of tactical aspects of match performance in soccer.